Soccer players cultural capital and its impact on migration - Krizaj, J.; Leskosek, B.; Vodicar, J.; Doupona Topic, M. (Journal of Human Kinetics, 2016)
The purpose of this study was to identify factors that constituted the cultural capital among soccer players. We assumed that in the increasingly globalized world of professional soccer, a player`s success would often depend on migrating and adjusting to life in other countries. Willingness to migrate and successful adjustment are tied to player`s previous attitudes and/or behaviours (habitus), significant support from others, including family members, and previous experiences and success in sports and education. Our hypothesised model of the cultural capital was based on the Pierre Bourdieu`s theoretical framework. It consisted of 26 variables related to three sets of factors: soccer experiences, a family context and support, and educational achievements of the players and their parents. The model was tested using a sample of 79 current soccer coaches who also had been players at the elite level. A factor analysis was used to empirically verify the content of the hypothetical model of the soccer players` cultural capital. Nine latent factors were extracted and together, they accounted for 55.01% of the total model variance. Individual factors obtained showed a sufficient level of substantial connection. The Cronbach`s alpha value of 0.77 confirmed the internal consistency of the operationalised variables in the hypothetical model. In addition, the impact of these aforementioned life dimensions on the migration of soccer players was studied. The results of the binary logistic regression analysis showed that the first factor of the hypothetical model (F1) had 2.2 times and the second factor (F8) had 3.9 times higher odds for migration abroad. Sociocultural findings using this new assessment approach could help create better "success conditions" in the talent development of young players